Consolidation of first remission using radioimmunotherapy with yttrium-90-ibritumomab-tiuxetan in adult patients with Burkitt lymphoma. Issue 3 (March 2015) - Koechli, Valentin; Klaeser, Bernd; Banz, Yara; Mueller, Beatrice U.; Pabst, Thomas
Highlights Radioimmunotherapy consolidation has not been reported in rituximab treated BL. In this series, none of 5 BL patients relapsed after Y-90-IT consolidation in CR1. OS and PFS in BL patients without or with Y-90-IT were not significant. Significant myelosuppression was seen in BL patients after Y-90-IT consolidation.